At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

f(x)=3x+3, then f^-1(x)=

Sagot :

Answer:

f^ - 1 (x) = x/3 + 1/3​ is not the inverse function of f(x) = 3x + 1

Step-by-step explanation:

F(x) = 3x + 1

Inverse:

x = 3y + 1

3y = x - 1

y = x/3 - 1/3 or f^ - 1 (x) = x/3 - 1/3​

so

f^ - 1 (x) = x/3 + 1/3​ is not the inverse function of f(x) = 3x + 1